Micro Steel Fiber Concrete Using Ultrasonic Pulse Velocity Method - Mohd Nizam, Muhammad Akmal Hakim; Shahidan, Shahiron (Recent Trends in Civil Engineering and Built Environment, 2023)
Concrete is a prevalent compound that has been used to advance human civilization all over the world. One of the ways to increase durability and sustainability for concrete is to use fiber as an additive and reinforcement in concrete. For information, fiber has been used in cementitious matrices for over 4500 years. Micro steel fiber, MSF, is one of the most often utilised fibers in concrete. Apart from that, structure health monitoring is one of the best ways that can be used to identify defects that occur in concrete structures. Among the method, ultrasonic pulse velocity, UPV, which is the non-destructive testing is the good method compare to others. The objective of this research is to determine the mechanical properties such as strength and wave velocity of micro steel fiber concrete due to the different percentages of micro steel fibers 0%, 0.5%, 1.0% and 1.5% using the ultrasonic pulse velocity method. Then, the optimum percentage of micro steel fiber in concrete will be decided according to the ultrasonic pulse velocity result. The first procedure of this research was preparing the concrete mixing material according to calculation using Department of Environmental, DoE, method. Then, the materials mixed and been curing for 7 days and 28 days. The ultrasonic pulse velocity test and compressive strength test has been carried out after the curing. Finally, the data has been analyse. In conclusion, the optimum percentage of micro steel fiber in concrete that has been obtained was 1.5% as it achieved the highest result for ultrasonic pulse velocity test and compressive strength test compared to control concrete.